Carrie angyal vagy démon? - Csetényi Korinna (Tudományos és művészeti műhelymunkák: új utakon a Pedagógusképző Kar című konferencia előadásai, 2009)
Employing a multiplicity of perspectives, King traces the story of an adolescent outcast. As a social horror story, it reveals the problems connected to maturation, the conservative nature of high schools and the dangers of religious fanaticism. This dark Cinderella story is about a girl feeling her powers for the first time and getting her revenge for her past humiliations.